Performance evaluation and selection of the core drill bits for lunar rock - Xuan Wang; Yan Wu; Zheng Gao; Haichun Hao; Lang Zhou; Jiahua Li; Mingzhong Gao (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract The objective of this study is to systematically examine the drilling efficiency and performance of various core drill bits in lunar rock formation using the discrete element method (DEM) and drilling experiments conducted in a lunar vacuum environment. This research aims to establish a scientific foundation for selecting core drill bits for lunar deep drilling operations. To achieve this, four distinct core drill bits were designed. Subsequently, a numerical model of lunar rock was constructed and the load characteristics and drilling efficiency of each bit during the drilling process were analyzed using DEM. Drilling and coring tests were then performed in both atmospheric and lunar vacuum environments, thereby validating the numerical simulation results and providing a comprehensive evaluation of the actual performance of the core drill bits. The study revealed that the carbide-tipped core drill bit with octagonal prisms design resulted in the core disking due to a significant rise in temperature, underscoring the critical importance of temperature control in maintaining core integrity. While the carbide-tipped core drill bit with cutting edges demonstrates exceptional drilling efficiency and coring quality, its inherent fragility and rapid wear of the cutting edges present considerable challenges for practical application. The diamond-impregnated core drill bit is unsuitable for drilling operations under lunar loads and power limitations due to its high weight-on-bit (WOB) requirements. In contrast, the PDC core drill bit exhibits excellent drilling stability, low rotary torque requirements, minimal temperature-rise effects, and significantly enhanced penetrating speed in the lunar vacuum environment, making it a recommended choice for lunar rock drilling. This study provides substantial theoretical and experimental support for the development of lunar drilling equipment and the formulation of effective drilling strategies.